Comparing the effectiveness of multisensory stimulation and cognitive rehabilitation on mental state, memory and sleep disorder in elderly women with cognitive impairments - Mostafavi, Masoumeh; Haydari, Shaban; Emadian, Seyedeh Olia (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of comparing the effectiveness of multisensory stimulation and cognitive rehabilitation on mental state, clinical memory and sleep disorder in elderly women with cognitive impairments. Methods: The current research was conducted as a semi-experimental pre-test-post-test type with control and follow-up groups. The statistical population consisted of 30 elderly women referring to nursing homes in Tehran, who were divided into two experimental and control groups by a simple random method. To collect data from Folstein mental state questionnaires (1975), Wechsler Bluber clinical memory questionnaire (1939), Petersburg Boyce et al. sleep quality questionnaire (1989) and cognitive deficits questionnaire (national surveys standard of the Ministry of Health and Iran Statistics Center) used. The data was analyzed using SPSS-21 software and mixed analysis of variance tests. Results: According to the results of multisensory stimulation and cognitive rehabilitation, it improves mental status (F=28.58, P